A model of stem cell population dynamics: in-silico analysis and in-vivo validation - Kugler, Hillel (Development, 2012)
The proper renewal and maintenance of tissues by stem cell populations is simultaneously influenced by anatomical constraints, cell proliferation dynamics and cell fate specification. However, their relative influence is difficult to examine in vivo. To address this difficulty we built, as a test case, a cell-centered state-based computational model of key behaviors that govern germline development in C. elegans, and used it to drive simulations of cell population dynamics under a variety of perturbations. Our analysis provided unexpected possible explanations for laboratory observations, including certain ‘all-or-none’ phenotypes and complex differentiation patterns. The simulations also offered insights into niche-association dynamics and the interplay between cell cycle and cell fate. Subsequent experiments validated several predictions generated by the simulations. Notably, we found that early cell cycle defects influence later maintenance of the progenitor cell population. This general modeling approach is potentially applicable to other stem cell systems.